2005
DOI: 10.1017/s0003161500069340
|View full text |Cite
|
Sign up to set email alerts
|

“I Heard it through the Grapevine”: Analysis of an Anti-Secularization Initative in the Sixteenth-Century Arequipan Countryside, 1584–1600

Abstract: Franciscan historian Antonine Tibesar’s study of the early evangelical accomplishments of the Franciscan Order in the Andes constitutes a landmark contribution to an insufficiently examined subject. Trying to detach his work from Joachimist debates, Tibesar did not deem the spirituality shared by peninsular friars to be relevant in explaining their poor early evangelical results. Although Tibesar acknowledged such shortcomings, he sustained that they were caused by an apathetic Franciscan engagement in parish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…María N. Marsilli, in her study of the Arequipan countryside, has shown that the support of the indigenous leadership of the Collagua and Cabana Indians for the antisecularization campaign of the late sixteenth century was motivated by many factors, including pre-Hispanic indigenous organization, the social ambitions of the Native elite and priests, and the economic ties that bound the Arequipan countryside to places like Lima and Potosí. 24 She shows that both the economic elite and priests depended upon maintaining good relations with the indigenous elite, who controlled access to labor and who could make or break an ambitious priest's career. Political and economic factors like these could be as limiting as cultural barriers and misunderstandings.…”
mentioning
confidence: 99%
“…María N. Marsilli, in her study of the Arequipan countryside, has shown that the support of the indigenous leadership of the Collagua and Cabana Indians for the antisecularization campaign of the late sixteenth century was motivated by many factors, including pre-Hispanic indigenous organization, the social ambitions of the Native elite and priests, and the economic ties that bound the Arequipan countryside to places like Lima and Potosí. 24 She shows that both the economic elite and priests depended upon maintaining good relations with the indigenous elite, who controlled access to labor and who could make or break an ambitious priest's career. Political and economic factors like these could be as limiting as cultural barriers and misunderstandings.…”
mentioning
confidence: 99%